Scope of implementation of food environment policy in Côte d'Ivoire and prioritization of actions using the Healthy Food Environment Policy Index (Food-EPI) - Tieissiehi, Dohe Franck; Etty, Marie-Christine; Konan, Amoin Georgette; Niaba, Koffi Pierre Valery; Kouassi, Francis; Manga, Julien Soliba; Moubarac, Jean Claude; Vandevijvere, Stefanie; Diouf, Adama; Assa, Rebecca Rachel (Progress in Nutrition, 2025)
Background and aim: The nutrition transition, marked by evolving dietary habits, has negatively impacted food systems in Côte d’Ivoire. This study evaluated existing public health nutrition policies and identified strategic interventions to foster healthier food environmentsMethods: This study was conducted using the Food-EPI tool, developed by the INFORMAS network and adapted to the Ivorian context. The tool comprises two core components (policy and infrastructure support), 13 domains, and 59 good practice indicators - including 12 novel indicators specifically addressing the double burden of malnutritionResults: Among the 59 indicators, the implementation level of nutrition policies in Côte d'Ivoire was rated as 'very low' for none, 'low' for 34, 'medium' for 24, and 'high' for only one. From the 115 identified actions, 20 were prioritized and recommended to the government for improving food environments. These actions specifically address school food environments, breastfeeding promotion, and nutrition financingConclusions: This study revealed low overall implementation of nutrition policies. Consequently, priority actions were identified to enhance food environments and effectively address the double burden of malnutrition in Côte d’Ivoire.